2019
DOI: 10.21608/bvmj.2019.14596.1040
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Zinc Oxide Nanoparticles in Fresh Meat

Abstract: Practical application of suspension with different concentrations (5mM, 8mM, and 10mM) were investigated to evaluate its antibacterial effect in fresh meat. A total number of 12 samples of fresh meat were collected from different abattoirs (150 gm. of each) in Gharbia Governorate, Egypt, under complete aseptic conditions and transferred without undue delay to the Lab to evaluate the efficacy of ZnO NPs as antibacterial agents in fresh meat. The obtained results indicated that ZnO-NPs had a significant inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Our data demonstrated that the highest inhibitory action of ZnO NPs was achieved by smaller size 20 nm with a higher concentration 10 mM against 10 5 CFU/mL S. aureus . The results were concordant with Saafan et al [ 40 ], who reported that size 20 nm achieved a high growth reduction 97.49% and 99.10% for S. aureus with 5 and 10 mM ZnO NPs, respectively at 24 h. However, decreased outcomes were achieved by Ibrahim et al [ 41 ], who reported that the highest growth reduction for S. aureus (10 7 CFU/mL) treated with a concentration 10 mM at sizes 50 and 20 nm ZnO NPs was 12.56% and 25.35%, respectively. The results here with Mirhosseini and Firouzabadi [ 38 ] showed that 20–25 nm at 5 mM ZnO NPs had a 33.9% growth decrease, which is lower than our results, while showing agreement with significant growth inhibition by 10 mM, which nearly totally stopped the growth of 10 7 CFU/mL S. aureus at 24 h. The probable mechanisms of action of metal nanoparticles could be: (a) excessive generation of reactive oxygen species within bacteria, (b) disturbance of key enzymes in the respiratory chain through microbial plasma membranes damage, (c) metal ion collecting in microbial membranes, (d) electrostatic attraction among nanoparticles of metal and microbial cells inhibits metabolic processes, and (e) suppression of microbial proteins/enzymes through improved production of H2O2 [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our data demonstrated that the highest inhibitory action of ZnO NPs was achieved by smaller size 20 nm with a higher concentration 10 mM against 10 5 CFU/mL S. aureus . The results were concordant with Saafan et al [ 40 ], who reported that size 20 nm achieved a high growth reduction 97.49% and 99.10% for S. aureus with 5 and 10 mM ZnO NPs, respectively at 24 h. However, decreased outcomes were achieved by Ibrahim et al [ 41 ], who reported that the highest growth reduction for S. aureus (10 7 CFU/mL) treated with a concentration 10 mM at sizes 50 and 20 nm ZnO NPs was 12.56% and 25.35%, respectively. The results here with Mirhosseini and Firouzabadi [ 38 ] showed that 20–25 nm at 5 mM ZnO NPs had a 33.9% growth decrease, which is lower than our results, while showing agreement with significant growth inhibition by 10 mM, which nearly totally stopped the growth of 10 7 CFU/mL S. aureus at 24 h. The probable mechanisms of action of metal nanoparticles could be: (a) excessive generation of reactive oxygen species within bacteria, (b) disturbance of key enzymes in the respiratory chain through microbial plasma membranes damage, (c) metal ion collecting in microbial membranes, (d) electrostatic attraction among nanoparticles of metal and microbial cells inhibits metabolic processes, and (e) suppression of microbial proteins/enzymes through improved production of H2O2 [ 42 ].…”
Section: Discussionsupporting
confidence: 93%